Short-term flooding increases CH4 and N2O emissions from trees in a riparian forest soil-stem continuum - Schindler, Thomas; Mander, Ülo; Machacova, Katerina; Espenberg, Mikk; Krasnov, Dmitrii; Escuer-Gatius, Jordi; Veber, Gert; Pärn, Jaan; Soosaar, Kaido (Scientific reports, 2020)
One of the characteristics of global climate change is the increase in extreme climate events, e.g., droughts and floods. Forest adaptation strategies to extreme climate events are the key to predict ecosystem responses to global change. Severe floods alter the hydrological regime of an ecosystem which influences biochemical processes that control greenhouse gas fluxes. We conducted a flooding experiment in a mature grey alder (Alnus incana (L.) Moench) forest to understand flux dynamics in the soil-tree-atmosphere continuum related to ecosystem N2O and CH4 turn-over. The gas exchange was determined at adjacent soil-tree-pairs: stem fluxes were measured in vertical profiles using manual static chambers and gas chromatography; soil fluxes were measured with automated chambers connected to a gas analyser. The tree stems and soil surface were net sources of N2O and CH4 during the flooding. Contrary to N2O, the increase in CH4 fluxes delayed in response to flooding. Stem N2O fluxes were lower although stem CH4 emissions were significantly higher than from soil after the flooding. Stem fluxes decreased with stem height. Our flooding experiment indicated soil water and nitrogen content as the main controlling factors of stem and soil N2O fluxes. The stems contributed up to 88% of CH4 emissions to the stem-soil continuum during the investigated period but soil N2O fluxes dominated (up to 16 times the stem fluxes) during all periods. Conclusively, stem fluxes of CH4 and N2O are essential elements in forest carbon and nitrogen cycles and must be included in relevant models.